To the inhabitants of the United States of America : Friends and countrymen. The present situation of public affairs demands your most serious attention, and particularly the great and encreasing depreciation of your currency . - Dickinson, John, 1732-1808 (LLMC-digital (Series), 1779)
June 9, 1779 publication in Connecticut of a Congressional address of May 26, 1779. The address discussed numerous topics, including the state of the war, taxation, and the need to raise necessary troops.